Deep Conceptual Learning in Physics Learning: A STEM-Based Waterwheel Project for High School Students’ Scientific Literacy - Rahmati, Rahmati; Syukri, Muhammad; Mentari, Mentari; Evendi, Evendi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Scientific literacy is a crucial competency in 21st-century education, encompassing students’ ability to understand scientific concepts, apply them in real-life contexts, and make evidence-based decisions. Despite various curriculum reforms, assessments such as PISA 2022 reveal that Indonesian students’ scientific literacy remains below the international average. Prior studies have applied Project-Based Learning (PjBL) and STEM approaches separately, yet few have explicitly integrated these with the Engineering Design Process (EDP) and local environmental contexts to systematically enhance scientific literacy. Addressing this gap, this quasi-experimental study examines the effectiveness of a PjBL-STEM model, contextualized by a waterwheel project utilizing local river flow, in fostering students’ deep conceptual learning and scientific literacy on the topic of Work and Energy. The study involved two purposively selected 11th-grade classes (N=60) at SMA Negeri 1 Samalanga: an experimental class taught with the PjBL-STEM-EDP approach and a control class taught conventionally. Instruments were validated (Cronbach’s alpha=0.926) and data were analyzed using t-tests, N-Gain, and effect size (Cohen’s d=2.25). Results showed the experimental group achieved significantly higher scientific literacy (mean post-test = 84.83 vs. control = 65.67; N-Gain = 0.83 vs. 0.49; t(58) = -8.71, p < 0.001, 95% CI [-23.6, -14.7]), with the strongest improvement in designing scientific investigations. The novelty of this study lies in aligning PjBL syntax, EDP stages, and OECD scientific literacy indicators within a local-context project. While deep conceptual learning (DCL) is used here as a theoretical framing rather than a measured outcome, the findings highlight the potential of contextual, interdisciplinary learning to foster scientific literacy, creativity, and critical thinking, supporting the goals of the Merdeka Curriculum and Education for Sustainable Development.